Are Alberta's Northern Pike Populations at Risk from Walleye Recovery?. (26th February 2021) - Paul, Andrew J.; Cahill, Christopher L.; MacPherson, Laura; Sullivan, Michael G.; Brown, Myles R.
Abstract: Angling catch rates of Walleye Sander vitreus in many lakes across Alberta have increased dramatically in the past 20 years, following their collapse and then recovery after implementation of restrictive harvest regulations. With increased abundance, some anglers are concerned that Walleyes may negatively affect abundance of Northern Pike Esox lucius . To address this hypothesis, we looked at net catch data for each species from 352 surveys in 129 lakes across Alberta between 2000 and 2017. Results were equivocal. Netting data indicated that low‐density Northern Pike populations were not associated with high densities of Walleyes when grouped categorically. However, mixed‐model quantile regression did support a negative relationship for the two species, but the mechanism is unclear and the strength of the interaction is weak in most cases. In few lakes (≤10%), potentially acceptable reductions in Walleye densities may produce meaningful increases in Northern Pike but uncertainty is substantial. Future Walleye harvest experiments to reduce uncertainty and establish causation are warranted only if Northern Pike are already at moderate to high densities and large reductions in Walleyes (≥75%) are acceptable. For these reasons, increased Walleye harvest is not supported as a management tool for increasing Northern Pike populations or enhancing angler catch rates in Alberta.